2018
DOI: 10.1021/acs.nanolett.8b04278
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Decoupling Co-Catalyst from a Photoabsorbing Semiconductor as a New Strategy To Boost Photoelectrochemical Water Splitting

Abstract: A cocatalyst is normally deposited on a photoabsorbing semiconductor (PAS) for photoelectrochemical (PEC) water splitting, but with drawbacks of limited loading, reduced light absorption, and tendency of charge recombination. To tackle these problems, a scheme of three-dimensional (3D) decoupling cocatalysts from the PAS with a pore-spanning crisscross conducting polymer host is proposed in this work. To demonstrate the concept, a facile method was developed for the in situ cogrowth of FeO x nanoparticles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…In this case, the distances among the catalyst islands need to be optimized to assure the minority carriers to be effectively collected and to avoid excess recombination of the majority carriers. Similarly, Long et al also demonstrated the benefit of a 3D electrocatalyst structure for the PEC performance of TiO 2 photoanodes via depositing FeO x NPs in a matrix of pore‐spanning conducting polymer (CP) on the surface of TiO 2 nanorod (NR) arrays . The photocurrent density of the resulting CP‐FeO x /TiO 2 was found to improve by a factor of 2.86 relative to that of the pristine TiO 2 NR array, at 1.23 V RHE .…”
Section: Semiconductor/electrocatalyst Interfacementioning
confidence: 93%
See 1 more Smart Citation
“…In this case, the distances among the catalyst islands need to be optimized to assure the minority carriers to be effectively collected and to avoid excess recombination of the majority carriers. Similarly, Long et al also demonstrated the benefit of a 3D electrocatalyst structure for the PEC performance of TiO 2 photoanodes via depositing FeO x NPs in a matrix of pore‐spanning conducting polymer (CP) on the surface of TiO 2 nanorod (NR) arrays . The photocurrent density of the resulting CP‐FeO x /TiO 2 was found to improve by a factor of 2.86 relative to that of the pristine TiO 2 NR array, at 1.23 V RHE .…”
Section: Semiconductor/electrocatalyst Interfacementioning
confidence: 93%
“…Another approach to reducing parasitic light absorption of electrocatalysts is to minimize the geometric footprint of the opaque electrocatalysts on the light‐absorbing surfaces of semiconductors . Constructing three‐dimensional (3D) electrocatalysts on the surface of semiconductor photoelectrodes can relax the constraint on the catalyst loading against catalyst footprint, and therefore decouple the light absorption of semiconductor and surface charge transfer.…”
Section: Semiconductor/electrocatalyst Interfacementioning
confidence: 99%
“…Comparing with ex situ composite technologies, in situ fabrication can achieve much better PEC performance, due to the tight contact between g‐C 3 N 4 and secondary material with reduced recombination centers at the interface, which is very beneficial to the separation and transport of photogenerated charges. More types of cocatalysts should be introduced into g‐C 3 N 4 ‐based heteroarrays for higher PEC performance. As well known, the cocatalysts can boost the PEC capability of photoelectrodes through either passivating the surface recombination or catalyzing the HER/OER 183,184 . For instance, Pt and IrO 2 (or RuO 2 ) exhibit the superhigh activity for HER and OER in a broad pH range, respectively 185‐187 .…”
Section: Summary Challenges and Perspectivementioning
confidence: 99%
“…The construction of nanoarray architectures, such as onedimensional nanowire arrays and two-dimensional (2D) nanosheet arrays, is regarded as an efficient approach to improve the PEC performance due to their various merits of elevated light absorption, shortened diffusion distance of minority carrier, and increased surface area for carrier collection and interfacial redox reactions [13][14][15][16] . Additionally, the hierarchical three-dimensional (3D) nanoarrays can be used to further enhance the PEC performance by increasing the light absorption and photoelectrode/electrolyte interface area [17][18][19][20][21] . On the other hand, however, the construction of semiconductor photocatalyts with 3D nanoarray structures will also bring about the remarkably increased surface defects.…”
Section: Introductionmentioning
confidence: 99%